Formarsi con la poesia di tre poeti: Pascoli, Saba, Montale - Franco Cambi (Studi sulla Formazione, 2025)
Pascoli, Montale and Saba are three poets capable of offering important lessons and proposing significant values, both in a human and poetic sense. The voices of these three authors are diverse and original, and their poems offer meaningful reflections on various ideal and lived experiences: they explore the very value of life, reinterpreting it with exquisite personal and human sensitivity. These are therefore three poetic voices that should be read and reread, precisely to enrich each person's awareness of themselves and of life itself.